Impact of Tyrosine Kinase Inhibitors Applied for First-Line Chronic Myeloid Leukemia Treatment on Platelet Function in Whole Blood of Healthy Volunteers In Vitro - Eckart, Falk; Tauer, Josephine T.; Suttorp, Meinolf; Knöfler, Ralf (Hämostaseologie, 2023)
The tyrosine kinase inhibitors (TKIs) imatinib, dasatinib, bosutinib, and nilotinib are established for first-line treatment of chronic myeloid leukemia (CML) but may cause side effects such as bleeding and thrombotic complications. We investigated the impact of TKIs on platelet function ex vivo in anticoagulated whole blood (WB) samples from healthy adults by lumiaggregometry and PFA-100 test. Samples (n = 15 per TKI) were incubated for 30 minutes with TKI at therapeutically relevant final concentrations. Aggregation and ATP release were induced by collagen (1 µg/mL), arachidonic acid (0.5 mmol/L), and thrombin (0.5 U/mL). Imatinib, bosutinib, and nilotinib significantly increased collagen-induced aggregation compared with controls. In addition, for bosutinib and nilotinib, a significant increase in aggregation after induction with arachidonic acid was detected. ATP-release and PFA-100 closure times were not influenced significantly by these three TKI. In contrast, dasatinib demonstrated a concentration-dependent inhibition of collagen-induced aggregation and ATP release and a significant prolongation of the PFA-100 closure time with the collagen/epinephrine cartridge. Aggregation and ATP release by other agonists as well as closure time with the collagen/ADP cartridge were not influenced significantly. In conclusion, we clearly show a concentration-dependent inhibition of collagen-induced platelet function in WB by dasatinib confirming prior results obtained in platelet-rich plasma. Bosutinib and nilotinib exerted no impairment of platelet activation. On the contrary, both TKI showed signs of platelet activation. When comparing our results with existing data, imatinib in therapeutic relevant concentrations does not impair platelet function.
Keywords: tyrosine kinase inhibitors; platelet pathology inherited/acquired; chronic myeloid leukemia; BCR-ABL1; primary hemostasis